Preventive role of exercise training in autonomic, hemodynamic, and metabolic parameters in rats under high risk of metabolic syndrome development - Moraes-Silva, Ivana Cinthya (2013)
Preventive role of exercise training in autonomic, hemodynamic, and metabolic parameters in rats under high risk of metabolic syndrome development. J Appl Physiol 114: 786-791, 2013. First published January 17, 2013; doi:10.1152/japplphysiol.00586.2012.-High fructose consumption contributes to metabolic syndrome incidence, whereas exercise training promotes several beneficial adaptations. in this study, we demonstrated the preventive role of exercise training in the metabolic syndrome derangements in a rat model. Wistar rats receiving fructose overload in drinking water (100 g/l) were concomitantly trained on a treadmill (FT) or kept sedentary (F) for 10 wk. Control rats treated with normal water were also submitted to exercise training (CT) or sedentarism (C). Metabolic evaluations consisted of the Lee index and glycemia and insulin tolerance test (kITT). Blood pressure (BP) was directly measured, whereas heart rate (HR) and BP variabilities were evaluated in time and frequency domains. Renal sympathetic nerve activity was also recorded. F rats presented significant alterations compared with all the other groups in insulin resistance (in mg.dl(-1).min(-1): F: 3.4 +/- 0.2; C: 4.7 +/- 0.2; CT: 5.0 +/- 0.5 FT: 4.6 +/- 0.4), mean BP (in mmHG: F: 117 +/- 2; C: 100 +/- 2; CT: 98 +/- 2; FT: 105 +/- 2), and Lee index (in g/mm: F = 0.31 +/- 0.001; C = 0.29 +/- 0.001; CT = 0.27 +/- 0.002; FT = 0.28 +/- 0.002), confirming the metabolic syndrome diagnosis. Exercise training blunted all these derangements. Additionally, FS group presented autonomic dysfunction in relation to the others, as seen by an similar to 50% decrease in baroreflex sensitivity and 24% in HR variability, and increases in sympathovagal balance (140%) and in renal sympathetic nerve activity (45%). These impairments were not observed in FT group, as well as in C and CT. Correlation analysis showed that both Lee index and kITT were associated with vagal impairment caused by fructose. Therefore, exercise training plays a preventive role in both autonomic and hemodynamic alterations related to the excessive fructose consumption.